2023
DOI: 10.1111/bcp.15660
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists for the treatment of pituitary tumours: From ergot extracts to next generation therapies

Abstract: They are the established first-line treatment for prolactinomas which express high levels of D2 receptors. Growing data support their use as an adjuvant treatment option for other pituitary tumours including growth hormone, adrenocorticotrophic hormones, thyroid hormone secreting adenomas and nonfunctional pituitary tumours, all of which have been shown to express D2 receptors as well, albeit to varying extents. For those pituitary tumours inadequately treated by dopamine agonist alone, combined agonism of D2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 252 publications
0
3
0
Order By: Relevance
“…Dopamine agonists are considered the first-line treatment for prolactinomas and idiopathic hyperprolactinemia ( 1 , 2 ). These agents act by binding to dopamine D2 receptors, which are highly expressed in prolactinomas ( 3 ). Two dopamine agonists are available in Brazil, i.e., bromocriptine and cabergoline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine agonists are considered the first-line treatment for prolactinomas and idiopathic hyperprolactinemia ( 1 , 2 ). These agents act by binding to dopamine D2 receptors, which are highly expressed in prolactinomas ( 3 ). Two dopamine agonists are available in Brazil, i.e., bromocriptine and cabergoline.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperprolactinemia secondary to antipsychotics should be treated when associated with hypogonadotropic hypogonadism due to the effects of hypoestrogenism. The following three management alternatives are possible in this situation: ( 1 ) change the medication that induced the hyperprolactinemia, ( 2 ) initiate hormone replacement therapy with estrogen, which should be associated with progestogen in patients with uterus, and ( 3 ) start a dopamine agonist (in this case, close monitoring is required, since the dopamine agonist and the antipsychotic may have opposing effects that increase the risk of exacerbation of the psychotic condition) ( 42 ). A recent literature review has shown that patients with hyperprolactinemia induced by antipsychotic medications may benefit from treatment with aripiprazole as a replacement or associated medication, since this antipsychotic does not cause hyperprolactinemia ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently microadenomas (< 1 cm in size) but approximately 40% are macroadenomas and a small minority are giant macroprolactinomas (> 4 cm in size) ( 4 ). In contrast to almost all other PAs in which transsphenoidal surgery (TSS) is the standard therapeutic modality, prolactinomas are primarily treated medically using dopamine agonists ( 5 , 6 ). However, about 10-20% of prolactinomas are resistant to dopamine agonist therapy ( 7 ).…”
Section: Introductionmentioning
confidence: 99%